Meningkatkan Keputusan Pembelian dengan Content Marketing dan Lifestyle - Prawitra, Ida Bagus Gde Abim; Swara, Ni Nyoman Adityarini Abiyoga Vena (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The customer's decision to buy the company's products is the key to the company's success to be able to develop its business. This will show that the products offered have value in the eyes of consumers. This study aims to determine the improvement of purchasing decisions with content marketing and lifestyle at the Indogrind Store. The research population is 988 consumers in 2021 and as many as 99 people will be selected as samples. The data analysis method used is the multiple linear regression method. From the analysis that has been done, it was found that content marketing and lifestyle are able to have a positive and significant influence in improving purchasing decisions. Suggestions for the research proposed are to improve content marketing and increase understanding of consumer lifestyles to improve purchasing decisions.